ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU FACED FILM KAYU LAPIS MERANTI (Shorea spp.) DI PT BASIRIH INDUSTRIAL - Melly Dwi Cahyanti; Diana Ulfah; Lusyiani Lusyiani (Universitas Lambung Mangkurat, 2020)
This study aims to: (1) Calculate the estimated use of raw materials faced by meranti plywood (Shorea spp.) In 2019, (2) Calculate economical raw material orders, (3) Analyze safety stock, and when reorder point, (4) Determine maximum storage. This research was conducted at PT. Basirih Industrial Banjarmasin, for 3 months. To analyze the data the estimated use of raw materials is done by the EOQ method (Economic Order Quantity). The calculation results revealed that the estimated use of raw materials faced with Meranti plywood film (Shorea spp.) In 2019 amounted to 16,120.20 m3, the number of economic orders in 2019 was 63 times with the purchase of raw materials of 253,9306 m3 for each one order, Rescue supplies needed in 2019 are 95.3552 m3 so that the production process continues smoothly. The re-ordering of raw materials faced by meranti plywood film is carried out if the raw material inventory is reached 308.8676 m3 with a distance of 5 days for 63 orders in 2019, the maximum storage required in 2019 is 349,2858 m3 for support the continuity of the production process.